2011
DOI: 10.1111/j.1439-0272.2010.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma reactive oxygen species-antioxidants relationship with varicocele grade

Abstract: This work aimed to assess seminal plasma reactive oxygen species (ROS)-antioxidants relationship with varicocele grade in infertile men with oligoasthenoteratozoospermia (OAT). The study included 89 infertile OAT men with varicocele divided into grade I (n = 22) and grade II (n = 43), grade III (n = 24) and compared with 20 healthy fertile controls. In their seminal plasma, two ROS parameters (malondialdehyde [MDA], hydrogen peroxide [H(2) O(2) ]) and four antioxidants (superoxide dismutase [SOD], catalase [Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 31 publications
1
39
1
Order By: Relevance
“…Increased Reactive Oxidative Species (ROS) levels in seminal plasma are strongly correlated with varicocele degree and are reported to decrease after varicocelectomy [20,21]. The present study also documented that varicocele degree are positively correlated with seminal plasma 8-OHdG level and sperm DFI in the varicocele group.…”
Section: Discussionsupporting
confidence: 68%
“…Increased Reactive Oxidative Species (ROS) levels in seminal plasma are strongly correlated with varicocele degree and are reported to decrease after varicocelectomy [20,21]. The present study also documented that varicocele degree are positively correlated with seminal plasma 8-OHdG level and sperm DFI in the varicocele group.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, several studies have shown higher MDA levels as lipid peroxidation markers in infertile men. Mostafa et al found higher levels of MDA in the internal spermatic venous blood compared to those in the peripheral fluid (32). Similarly, in a study by Altunoluk et al, MDA levels were greater in the varicocele group (33).…”
Section: Discussionmentioning
confidence: 83%
“…ROS has been found in the seminiferous tubules and seminal plasma of most infertile patients, especially those with OAT. 20 The concentration of malondialdehyde, a marker of lipid peroxidation, was almost twice as high in the sperm pellet suspensions of men with asthenozoospermia and oligoasthenozoospermia as those with normozoospermia. 21 Previously, O'Bryan et al described CLU as present only in human abnormal spermatozoa, 14 in accord with the consensus that in defective semen samples high ROS generation is associated with decreased seminal antioxidants.…”
Section: Discussionmentioning
confidence: 99%